UJI EFEKTIVITAS SEDIAAN HAND SANITIZER EKSTRAK DAUN KEMANGI (Ocimum sanctum.L) TERHADAP Staphylococcus aureus - taufiq taufiq (Akademi Farmasi Yamasi Makassar, 2025)
This study aims to determine whether the hand sanitizer preparation of basil leaf extract (Ocimum sanctum.L) has an antibacterial effect against Staphylococcus aureus at concentrations of 1%, 2% and 4%. Basil leaf extract is made in hand sanitizer preparations with concentrations of 1%, 2% and 4%. This test used experimental methods in the Microbiology Laboratory of the Yamasi Pharmaceutical Academy, then tested the antibacterial effectiveness of the basil leaf extract hand sanitizer preparation (Ocimum Sanctum.L) . Then observations were made by measuring the zone of inhibition that existed at each concentration of the preparation for the test bacteria Staphylococcus aureus. The results obtained showed that the inhibition zone of 1% concentration had a diameter of 2.88 mm, 2% concentration had a diameter of 3.44 mm, and 4% concentration had a diameter of 5.14 mm. With the results of inhibiting bacterial growth which are categorized (weak < 5 mm, medium 5-10 mm). The conclusion of this study states that the hand sanitizer preparation of basil leaf extract (Ocimu sanctum.L) with a concentration of 4% is better than concentrations of 2% and 1%.